2020
DOI: 10.1002/ca.23691
|View full text |Cite
|
Sign up to set email alerts
|

Is variation in posterior tibial veins a risk factor for deep‐vein thrombosis?

Abstract: Introduction: This study proposes variations in the posterior tibial vein as one of the risk factors for deep-vein thrombosis. Understanding the anatomical classification of the posterior tibial vein would guide the antegrade approach of catheter-directed thrombolysis.Materials and methods: One hundred thirty-four legs from Korean and Thai cadavers were dissected. The posterior tibial veins were classified into four types according to the number of proximal and distal veins.Results: The most common type was ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Proximal and distal posterior tibial veins were de ned in accordance with previous research 5 . According to Yi & Kim, the proximal tibial vein begins from the point where the distal posterior tibial vein and peroneal vein merge, and it turns into the popliteal vein at the point where the anterior and proximal tibial veins merge (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal and distal posterior tibial veins were de ned in accordance with previous research 5 . According to Yi & Kim, the proximal tibial vein begins from the point where the distal posterior tibial vein and peroneal vein merge, and it turns into the popliteal vein at the point where the anterior and proximal tibial veins merge (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…Many clinicians suggest practitioners should consider anatomical variations as a risk factor for DVT. Thereby, previous study identi ed and classi ed the anatomical variation in the deep calf veins (Figure 1) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies that explain BoNT injection locations by navigating intramuscular neural distribution with naked eye dissection have limits, such as perceiving minuscule nerves and the likelihood of neural damage [17,21,25,[41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study identified and classified the anatomical variation in the deep calf veins (Fig. 1 ) [ 29 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%